HADIS TEMATIK TENTANG MENANAMKAN NILAI AKHLAK PADA ANAK DIDIK DALAM PENDIDIKAN ISLAM - Yanti Kusuma (EDURELIGIA: Jurnal Pendidikan Agama Islam, 2021)
This article discusses the hadith about instilling good moral values in children in Islamic education. Morals are a picture of a person's faith, the better one's faith, the better one's morals will be. For this reason, a teacher or parent must know what to teach a student and how the method has been guided by the Prophet Muhammad. Aim to form a good, responsible, and morally good person. Examples of hadiths that explain the cultivation of moral values in children are traditions about instilling generosity, honesty, almsgiving, birul walidain, the importance of studying, and others.